Coastal Palaeogeography of Akrotiri Peninsula, Cyprus. - Polidorou, M.; Evelpidou, N. (New Technologies, Hazards and Geoarchaeology - Paolo Pirazzoli in memoriam, 2017)
Akrotiri peninsula is located 5km W of the city of Lemesos and is the southernmost part of the island of Cyprus. Akrotiri peninsula consists of Quaternary sediments which are unconformably deposited on Miocene Pachna formation (chalks and marls). The Quaternary sediments include marine and associated aeolian deposits, alluvial fans and lagoonal and deltaic sediments.  Quaternary marine deposits occur as raised marine terraces with arenitic composition and they are located between elevations of 2-3m and 16-18m amsl. Quaternary alluvial fans were formed by material from the Kouris River, the largest river in Cyprus, and contributed to the formation of a western tombolo, resulting in a bay in antiquity. Local tectonics and eustatic changes resulted in the creation of Holocene geomorphological features, predominately, a salt lake, with an average water table of about 2 m below MSL, which is surrounded by uplifted marine terraces and lagoonal sediments. Based on geomorphologic mapping of the Quaternary landforms and associated deposits, and the morphosedimentary analysis of the geomorphological features, a chronostratigraphic framework for the Holocene evolution of the area has been generated. Textual references of Akrotiri peninsula first appear in Roman time by geographer Strabo who is describing it as a peninsula – like place. In Venetian and Ottoman maps is depicted the evolution of the area, the formation of the eastern tombolo and the usage of the closed lake as a fishery. Also, the diversion of Kouris River by Saint John’s knights west of the village of Kolossi, assisted the production of Sugar Cane and influenced the topography of the area.